Describing Point of Entry into Care and Being Lost to Program in a Cohort of HIV Positive Pregnant Women in a Large Urban Centre in Uganda. (2nd April 2017) - Musomba, Rachel; Mubiru, Frank; Nakalema, Shadia; Mackline, Hope; Kalule, Ivan; Kiragga, Agnes N.; Ratanshi, Rosalind Parkes; Castelnuovo, Barbara
Abstract : Introduction . We aim to describe the time of entry into care and factors associated with being lost to program (LTP) in pregnant women on Option B Plus in an integrated HIV and antenatal care (ANC) clinic in Uganda. Methods . We included all pregnant women enrolled into the integrated HIV-ANC clinic from January 2012 to 31st July 2014, while the follow up period extended up to October 30th 2015. LTP was defined as being out of care for ≥3 months. Results . Overall 856 women were included. Only 36.4% (86/236) of the women were enrolled in the first trimester. Overall 69 (8.1%) were LTP. In the multivariate analysis older women (HR: 0.80 per five-year increase, CI: 0.64–1.0, andP = 0.060 ) and women on ART at the time of pregnancy (0.58, CI: 0.34–0.98, andP = 0.040 ) were more likely not to be LTP. Among women already on ART at the time of pregnancy no factor was associated with LTP. Conclusion . Our results suggest the need for interventions to enhance prompt linkage of HIV positive women to HIV services for ART initiation and for increased retention particularly in young and ART naive women.